Myasthenia gravis AChR antibodies inhibit function of rapsyn-clustered AChRs. Issue 5 (12th March 2020) - Cetin, Hakan; Webster, Richard; Liu, Wei Wei; Nagaishi, Akiko; Koneczny, Inga; Zimprich, Fritz; Maxwell, Susan; Cossins, Judith; Beeson, David; Vincent, Angela
Abstract : Objective: Direct inhibition of acetylcholine receptor (AChR) function by autoantibodies (Abs) is considered a rare pathogenic mechanism in myasthenia gravis (MG), but is usually studied on AChRs expressed in cell lines, rather than tightly clustered by the intracellular scaffolding protein, rapsyn, as at the intact neuromuscular junction. We hypothesised that clustered AChRs would provide a better target for investigating the functional effects of AChR-Abs. Methods: Acetylcholine-induced currents were measured using whole-cell patch clamping and a fast perfusion system to assess fast (<2 min) functional effects of the serum samples. The sensitivity, specificity and rapidity of the system were first demonstrated by applying maternal AChR-Ab positive plasmas known to inhibit fetal AChR function in TE671 cells. Eleven previously untested AChR-Ab positive MG sera, 10 AChR-Ab negative MG sera and 5 healthy control sera were then applied to unclustered and rapsyn-clustered human adult AChRs in CN21 cells. Results: The maternal AChR-Ab positive plasmas reduced fetal AChR currents, but not adult AChR currents, by >80% within 100 s. Only 2/11 AChR-Ab positive sera inhibited AChR currents in unclustered AChRs, but 6/11 AChR-Ab positive sera compared with none of the 10 AChR-Ab negative sera (p=0.0020) inhibited rapsyn-clustered AChR currents, and current inhibition by the AChR-Ab positive sera was greater when the AChRs were clustered (p=0.0385). None of the sera had detectable effects on desensitisation or recovery from desensitisation. Conclusion: These results show that antibodies can inhibit AChR function rapidly and demonstrate the importance of clustering in exploring pathogenic disease mechanisms of MG Abs.